Menggali Genealogi dan Transformasi Vihara Sima 2500 Buddha Jayanti: Dari Situs Sejarah ke Pusat Spiritualitas Modern - Maulidah, Farikhatul; Gunawan, Muhammad; Rohmiyati, Yuli; Pramudyo, Gani Nur; Irhandayaningsih, Ana; Bramiana, Chelly Novia (Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
This study examines the genealogy, history, and transformation of Vihara Sima 2500 Buddha Jayanti as a center of spirituality and social engagement within the context of the Buddhist revival in Indonesia. Established in 1958 to commemorate 2500 years of the Buddha's passing, the vihara plays a strategic role in strengthening national and international religious and cultural networks. Using a qualitative and descriptive-analytical approach, this research reveals the process of revitalizing the vihara from its period of prominence through decline, to its renewed function as a meditation and community development hub that is open and inclusive. The findings indicate that the vihara functions not only as a place of worship but also as a social, educational, and multicultural space capable of addressing modern societal challenges. This revitalization demonstrates that traditional religious institutions can successfully build relevant spiritual identities and respond to Indonesia's social dynamics.